The Comparative Study of Unfocused Tasks and Focused Tasks in Improving Student’s Oral English Production - Yusmalinda Yusmalinda (LINGUA LITERA : journal of english linguistics and literature, 2015)
This study aimed at analyzing the effectiveness unfocused tasks and focused tasks in improving students’ oral English production. Because these unfocused tasks and focused tasks focus on meaning, not on form, they are strong version of communicative language teaching. The research questions of this research are: (1) is there a significant difference of students’ oral English production between students who are taught through unfocused tasks and students who are taught through focused tasks? (2) What problems do students find to speak English unfocused tasks? (3) What facilitates students to speak English in unfocused tasks? (4) What are the solutions of problems found in unfocused tasks? This was a mixing method research where of the three types of mixed methods researchdesigns, the QUAN-qual model (the explanatory mixed methods design) was used. In this model, experiment and descriptive methods were used. This reserach was done at STBA Prayoga Padang where two groups of students at the same level were involved. One group was taught through unfocused tasks and the other group was taught through focused tasks. After doing the reserach, it was found that unfocused tasks and focused tasks can improve students’ oral English production. It was found that unfocused tasks have better effect on students’ oral English fluency and focused tasks have better effect on students’ oral English accuray in terms of grammar. However, unfocused tasks have better effect than focused tasks on students’ oral English production. In other words, there was a significant difference of oral English production of students who were taught through unfocused tasks and students who were taught though focused tasks.